CROSS-BORDER COOPERATION BETWEEN UKRAINE AND THE EU: SOCIO-ECONOMIC IMPACTS AND PROSPECTS - STEGNIY, Serhiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the socio-economic consequences and prospects of cross-border cooperation (CBC) of Ukraine with the countries of the European Union in the context of deepening European integration processes. Theoretical and methodological approaches to understanding the essence of CBC as an instrument of regional development and European integration are considered. The impact of cross-border cooperation on key socio-economic parameters of the border regions of Ukraine is analyzed, in particular, the level of employment, investment attractiveness, infrastructure development, migration flows and quality of life of the population. In particular, based on the analysis of statistical data of the State Statistics Service of Ukraine and reports of the European Commission, it was found that in the regions covered by CBC programs, over the past 5 years, the level of capital investments has increased by 18.5%, and the share of small and medium-sized businesses in the structure of the economy has increased by 12.3%. The Poland-Belarus-Ukraine 2014-2020 Programme financed over 170 projects, 60% of which were aimed at infrastructure and sustainable development. Additionally, the article uses GIS analysis of border areas and spatial visualization of the impact of TCC on socio-economic parameters. Particular attention is paid to the institutional and legal aspects of the implementation of cross-border cooperation, as well as factors limiting its effectiveness: asymmetry of economic potential, bureaucratic barriers, fragmentation of regulatory support and geopolitical challenges, in particular in connection with the war in Ukraine. Promising directions for improving TCC policy at the national and regional levels are identified: harmonization of the legislative framework, expansion of participation in European programmes, creation of cross-border innovation clusters, increasing the role of communities in the implementation of projects. Based on a comprehensive analysis, it is concluded that cross-border cooperation plays a key role in the modernization of border regions, promotes social cohesion, expands the European area of stability, and also serves as a catalyst for internal reforms in Ukraine in the context of gradual approximation to EU membership.